Progressões denudacionais na vila São Rafael, zona norte de Santa Maria – RS - Marques, Rodrigo Diniz (2018)
This work projects the relief in the future through denudational progressions and retreat from the Itagiba slope in Vila São Rafael, Northern Zone of Santa Maria - RS. In this thesis, emphasis was given to the erosive and denudational processes occurring in a differentiated way in the soil surface layer by lithological influence on the physical-water parameters of the surface layer of the soil seated on the Caturrita Formation and Santa Maria Formation - Alemoa Member, eroding and denuding the relief in a different way. The work is justified because, in this area, there are two lithological formations, there has been a topographic cut for the installation of railroad and human occupation. The relief included the 4th taxon (denudation of the hill), the 5th taxon portions east and west - lithological differences and retreat of the Itagiba slope (south slope) and the 6th taxon that analyzed differentiated erosive and denudational processes: ridges, ravines, landslides (ROSS , 1992). The work was guided by the deductive method following the levels: compilatory, correlative, semantic and normative according to Libault, (1971). P1, 2P, 3P, 4P, 5P, 6P, P7, and P8 were collected in order to understand and later analyze the study area, , the samples were submitted to the Inderbitzen test adapted under a simulation of 20 mm precipitation in 3 hours, after which the laboratory data of loss of eroded sediments (height of the eroded sediments) were generalized by mathematical equations (Tales Theorem). the denudational progression maps and the recoil map of the Itagiba slope were constructed at 1, 10, 25, 75, 100 and 1000 years. The results obtained in the physical-water parameters showed a particle size distribution of points 2 and 3 (P2 and P3), indicating a clay concentration with a mean of 44.22% in these two points on the Santa Maria Formation. Alemoa indicating that this factor is a differentiating conditioner of the erosive processes, denudational progression and retreat of the Itagiba slope higher in the eastern portion compared to the western portion of the Itagiba slope dissecting the relief under the Santa Maria Formation - Alemoa Member about 3,033 times more (Table 1). In addition, the volume of sediments eroded from the surface soil samples collected on the Caturrita Formation (v1, v6, v7 and v8) at the four points presented mean values of 0.234 cm³, mean of sediment loss for the four surface soil samples (v2, v3, v4 and v5) that and were withdrawn on the Santa Maria - Alemoa Formation which was approximately 0.699 cm³. The denudation in 1000 (thousand) years - mean decrease of the areas represented by the points (P1, P6, P7 and P8), under the Caturrita Formation, presented average values of decrease of altitude of 253 cm, therefore, also smaller in relation to (P2, P3, P4 and P5) that represent areas settled on the Santa Maria Formation - Alemoa Member, which was 767 cm. It is concluded, therefore, that the eastern portion of the Itagiba slope, an area settled on the Santa Maria - Alemoa Formation, is the area of greatest susceptibility to erosion and denudation and that the factor that conditions this greater susceptibility to erosion and denudation, is the presence of clay (smectic 2: 1), which is counter-contagious and expansive, showing in the absence of moisture resistant to erosion, but when saturated, it erodes and denudes the relief about 3,033 times more than the areas settled on the Caturrita Formation (MACIEL FILHO, 1990 ). Finally, this work spatializes the behavior of the Itagiba hillside in order to alert public agencies to decision making.